Revolutionizing Financial Services: A Deep Dive into Salesforce AI Applications - Raviteja Pachika (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Salesforce’s artificial intelligence solutions in the financial services sector. The article examines the implementation of advanced AI technologies across various domains, including wealth management, loan processing, fraud detection, and customer support. The article highlights the significant improvements in operational efficiency, risk management, and customer experience through AI integration. The article covers the technical architecture of Salesforce’s AI solutions, emphasizing their microservices-based approach and future developments in hyper-personalization and predictive analytics. The article demonstrates how AI implementations are reshaping traditional banking operations while ensuring enhanced security and regulatory compliance.